2017
DOI: 10.11604/pamj.2017.27.74.7266
|View full text |Cite
|
Sign up to set email alerts
|

Birth preparedness and complication readiness among pregnant women in Osogbo Metropolis, Southwest Nigeria

Abstract: IntroductionHigh maternal mortality is a major problem in Nigeria. Birth Preparedness and Complication Readiness will ensure that women can have professional delivery thus reducing obstetric complications. This study assessed the birth preparedness and complication readiness among pregnant women in Osogbo metropolis, a south western community in Nigeria.MethodsA community based descriptive cross sectional survey was used. A total of 180 women were selected using multistage sampling technique. Pretested semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 10 publications
10
17
1
Order By: Relevance
“…Low compliance of ANC worldwide is considered as a hurdle for maternal and neonatal child health programs. In Nigeria, seventy-one percent of pregnant women are aware of the danger signs [10].…”
Section: Introductionmentioning
confidence: 99%
“…Low compliance of ANC worldwide is considered as a hurdle for maternal and neonatal child health programs. In Nigeria, seventy-one percent of pregnant women are aware of the danger signs [10].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, 65% and 73% of the Kenyan and Tanzania women set aside funds, respectively. The proportion was reported lower in other studies that showed 84.1% of women in central Tanzania [13], 87.5% in Rwanda [6] and 92.4% in Nigeria [41]. Central Tanzania hosts the county capital and is a high-income area, with better access to healthcare.…”
Section: Discussionmentioning
confidence: 67%
“…West Nigeria [41]. This could be explained by differences in the implementation of focused antenatal care and BPCR within a country and across countries [13].…”
Section: Discussionmentioning
confidence: 99%
“…Interventions to encourage birth preparedness and complication readiness during pregnancy have been strongly recommended by the World Health Organization (WHO) to promote timely utilization of SBA at childbirth [21]. Birth preparedness can be encouraged by increased maternal knowledge about danger signs; therefore, appropriate health education and counselling during ANC are considered to be a key intervention [5,6]. Moreover, better communication between health workers and mothers is believed to play an important role in building mutual trust, which is essential for acceptability [26].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this successful overall expansion of health care coverage, service utilization remains low in some regions and countries, and widening inequality in service usage has increasingly become a problem [3]. It has been reported that the disadvantaged women had limited access to health service [4][5][6]. Worldwide, 303, 000 mothers died in 2015 and 2.5 million neonates died in 2017, mostly of preventable causes and due to poor quality maternal and neonatal care [7][8][9].…”
Section: Introductionmentioning
confidence: 99%